FISERMAN SURVIVAL STRATEGY IN THE EAST MONSOON AND FAMILY WELFARE (Study in Haria Village Saparua District Central Maluku Regency) - Hobarth Williams Soselisa (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
Haria Village fishermen are still classified as traditional fishermen (small fishermen). This can be seen from the fact that some fishermen still use (small) outboard motor boats and very simple fishing gear such as bags, nets, and others. Haria's village fishermen consist of several types of fishermen, namely labor/worker fishermen, skipper fishermen, and private fishermen.the purpose of this research is to find out and analyze the strategies of the fishermen in fulfilling the needs of life in the East Season.This type of research is descriptive qualitative. Data collection methods are observation, in-depth interviews, and documentation studies. Data is collected from State Government and Fishermen.The research results prove that meeting basic needs is an act of fulfilling economic needs that are socially situated and inherent in the ongoing personal social network of actors. Structure plays an important role in determining individual decisions in fulfilling their life needs, whether it is the owner of a motorcycle, massnait or those who produce catches. Network strategy is a form of spontaneous order that arises as a result of various interactions between actors without being created by authority, but by a shared need to achieve beneficial social relations for welfare purposes.